Modulation of Noradrenergic Neurotransmission in Isolated Rat Radial Artery - Ana Cristina Martínez; Rosa María Pagán; Dolores Prieto; Paz Recio; Albino García-Sacristán; Medardo Hernández; Sara Benedito (Elsevier, 2009)
The present study was designed to characterize the neurogenic contraction of rat radial artery. Electrical field stimulation (EFS) evoked frequency-dependent contraction that was abolished by tetrodotoxin (neuronal Na+ channel blocker), guanethidine (sympathetic neuron blocker), or phentolamine (α-adrenoceptor blocker). The α1-adrenoceptor antagonist prazosin inhibited endothelium-independent contractions to EFS, noradrenaline (NA), and the α1-adrenoceptor agonist phenylephrine. Rauwolscine, an α2-adrenoceptor antagonist, augmented nerve-mediated contractions and reduced sensitivity to NA and the α2-adrenoceptor agonist BHT-920. The β-adrenoceptor antagonist propranolol diminished EFS-elicited contractions, while sensitivity to NA was enhanced by propranolol. Relaxations evoked by isoproterenol, a β-adrenoceptor agonist, were abolished by propranolol. NG-Nitro-L-arginine (L-NOARG), a nitric oxide (NO) synthase inhibitor, increased both nerve-mediated and NA-induced responses in endothelium-intact, but not in endothelium-denuded arteries. Moreover, endothelium-dependent responses to BHT-920 and isoproterenol were modified by L-NOARG. Tetraethylammonium (TEA) or 4-amynopyridine, the Ca2+-activated (KCa) or voltage-dependent K+ (KV) channel blockers, respectively, enhanced the neurogenic contractions observed. TEA but not 4-amynopyridine increased NA-induced contractions. The ATP-sensitive K+ (KATP)-channel blocker glibenclamide failed to modify adrenergic contractions. Blockade of capsaicin-sensitive primary afferents increased EFS-induced contractions. In conclusion, adrenergic contractions are predominantly mediated by muscular α1-adrenoceptors, while endothelial α2- and β-adrenoceptors play a minor role. Presynaptic α2- and β-adrenoceptors cannot be precluded. Noradrenergic neurotransmission in rat radial artery seems to be modulated by both stimulation of endothelial NO, KCa, and KV channels and sensory C-fiber activation. Keywords:: rat radial artery, electrical field stimulation, adrenergic receptor, nitric oxide, K+ channel